Exploring the Nutritional and Functional Value of Karonda (Carissa carandas): an Underutilized Fruit - Bai, Govindamma M.; Devi, Nimala G.; Lakshmi, K.; Bhagyalakshmi, K. (International Journal of Economic Plants, 2026)
The experiment was conducted during July, 2024–September, 2024 at Department of Food Science and Nutrition, ANGRAU-College of Community Science, Lam, Guntur, Andhra Pradesh, India to assess the physicochemical, nutritional, and functional properties of karonda fruits at four developmental stages: immature, mature (half red–half white), red ripe, and purple ripe. Karonda (Carissa carandas), an underutilized fruit known for its nutritional and therapeutic potential. Fruit dimensions increased significantly during ripening, from 2.12×1.55 cm2 (length×width) in immature fruits to 2.77×2.47 cm2 in purple ripe fruits, along with an increase in fruit weight from 3.03 g to 6.24 g. Total soluble solids rose from 5.35°Brix to 9.26°Brix, while titratable acidity declined from 4.21% to 2.93%. Total sugars increased from 1.11% to 5.34%, and reducing sugars from 0.54% to 3.27%. Ascorbic acid showed a marked rise from 5.12 mg 100 g-1 to 34.28 mg 100 g-1 with ripening. Proximate composition revealed a decrease in crude fiber (1.66% to 0.75%) and fat (2.61% to 2.00%), while protein content increased from 0.40% to 0.91%. Functional properties improved substantially, as reflected by increases in total phenolics (68.22 to 179.10 mg GAE (100 g-1), total flavonoids (134.74 to 242.44 mg RE (100 g-1), FRAP (7.01 to 31.69 mg TE (100 g-1), and DPPH activity (86.23 to 283.42 mg TE (100 g-1). Strong positive correlations were found among phenolics, flavonoids, vitamin C, and antioxidant activity (r=0.86–0.98). These findings indicated that purple ripe karonda fruits possessed the highest nutritional and antioxidant value, supporting their potential use in functional foods, value-added products, and nutraceutical applications.